Effects of morphology and graphitization of carbon nanomaterials on the rheology, emulsion stability, and filtration control ability of drilling fluids - Razali, Siti Zulaika; Yunus, Robiah; Kania, Dina; Abdul Rashid, Suraya; Ngee, Lim Hong; Alsultan, Abdulkareem Ghassan; Mohamed Jan, Badrul (Elsevier, 2022)
Nanomaterials are good potential additives in drilling fluid to improve the thermal and physical-mechanical properties of the fluids, but their use in this field is still scarce. Ester-based drilling fluid (EBDF) is an environmentally friendly drilling fluid. However, its use is still restricted to low to moderate drilling temperatures due to its poor thermal and hydrolytic stability. This study investigates the roles of morphology and graphitization of carbon nanomaterials on the rheology, filtration, and emulsion stability of EBDF at high pressure high temperature (HPHT) drilling conditions. Various carbon nanomaterials were investigated, including graphene nanopowder, commercial graphene nanoplatelets, in-house graphene nanoplatelets, graphene oxide, and carbon nanotubes cotton. The results showed that the behaviour of EBDF depended on the morphology and graphitization of carbon nanomaterials. Graphene nanopowder demonstrated the best performance due to its large size, low graphitic defect count, and most hydrophobic surface, which improved the EBDF emulsion stability and HPHT filtration properties. Hydrophobic surface of graphene nanopowder sheets provides superior protection against thermal degradation of the emulsifier films in drilling fluid. Filtration tests revealed that graphene nanopowder reduced the filtrate and filter cake thickness by 20% and 25%, respectively, at a graphene concentration of 0.007 wt%.